National Digital Library initiative in Korea - Ryu , Hee-kyeung (Persatuan Pustakawan Malaysia, 2009)
In order to create a library use environment adequate for the Digital Age, the National Library of Korea has created a physical structure which provides collection, organization, preservation and information viewing services and the Dibrary portal which is an integrative search environment of digital resources. The National Library of Korea has prepared selection policy for the collection of digital resources and established a cooperative network for the sharing of digital information to lead cooperative works between domestic and foreign institutions and provide 116 million numbers of digital contents via Dibrary main portal and 4 sub portals (Regional, Policy Information, Multicultural and portal for the Disable).